ALTERNATIF PENYELESAIAN SENGKETA TANAH MELALUI MEDIASI ANTARA YAYASAN MU’ADZ BIN JABAL DENGAN PEMERINTAH DESA SAWAH KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Kaspul Ilmi; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The dispute is basically a problem that often occurs in the global era of society atthe present moment either the individual dispute vertically, also the individualhorizontally as well as the existing groups within the community, therefore every issue ordispute of course have a way of settling either through litigation and non litigation.By way of mediation, it is expected that the settlement of a dispute becomescontrolled and does not harm any party to produce an agreed agreement that isunderstood and executed by the parties, in the settlement of this land case involving thegroup in the form of Foundation with the Village Government which is the organizer ofthe government in the village a phenomenon, which raises an important question as towhether using the mediation path can result in an effective resolution perceived by bothparties even more so if the dispute occurs between the public and the ruler vertically.The purpose of this study is to determine whether the obstacles in theimplementation of mediation between the Foundation with the Village Government andhow the effectiveness of the implementation of Mediation between Mu'adz Bin JabalFoundation with the Village Government of Kampar north Kampar districtThe data used in this study consisted of primary data and secondary dataobtained from field research results through interviews with resource persons fromMu'adz Bin Jabal Foundation and Village Government, and conducted literature studyon primary, secondary and tertiary legal materials related to theme research. Based onthe results of the above research, it can be concluded that the constraints in theimplementation of such mediation is sourced from the internal factors of the disputedparties, the object of the disputed object and external factors originating from partiesoutside the disputed parties. Then the dispute between the two parties has so far beenresolved through an alternative dispute resolution through consensus or mediation ingood faith so as to facilitate a settlement for both parties, although it can be said that theimplementation is not very effective for one of the parties to the disputeKeywords: Mediation, Dispute, Mediation Barriers